Modification of gold surfaces for the oriented immobilization of recombinant form of horseradish peroxidase - Matheus, Pedro Rafael; Abad, José María; Fernández, Víctor Manuel (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Gold threads of 0.50mmof diameter and 25mmin length were used as work electrodes. These electrodes were electrochemically characterized and their effective areas were determined. The gold surface was chemically modified with a self-assembled monolayer of thiols (SAMs) and, by means of successive reactions, they get bonded covalently to the thiols monolayer, ligands with chelates metallic ion groups (derived from the nitrilotriacetic acid, ANTA) which show affinity by surface receptors generated in a genetic enzyme via engineering techniques. The obtained results showed the good sensitivity, specificity and stability of the used electrochemical techniques in this work.